Riley's ghost - Anderson, John David, 1975- (Walden Pond Press, 2022)
Riley Flynn is having a hard time fitting in ever since her best friend, Emily, ditched her for the cool girls. But when her bullies lock Riley in the science closet after hours, she finds herself in a strange situation. After escaping from the closet, she discovers all the doors and windows of the school are locked, the phones are dead, and the lights aren't working. As she searches for a way out, Riley starts to feel like she's not alone, and she wonders if there could be a ghost haunting the school.